EFL TEACHER’S REFLECTION ON USING BAAMBOOZLE: BENEFITS, CHALLENGES, AND FUTURE IMPLEMENTATION - Lailatun Nisvi Rizki Amalia; Bambang Yudi Cahyono (ENGLISH EDUCATION STUDY PROGRAM, FACULTY OF TEACHER TRAINING AND EDUCATION, UNIVERSITAS SRIWIJAYA, 2024)
This study investigated an EFL teacher's reflection on benefits, challenges, and future implementation after integrating Baamboozle in the teaching of English to EFL students as reflected in the research questions: (1) what are the perceived benefits of using Baamboozle in teaching English to the sixth graders?; (2) What challenges does the teacher face when integrating Baamboozle into English lessons for the sixth graders?; and (3) How does the teacher plan to apply Baamboozle in future English language instruction?. A case study design was employed involving an EFL elementary school teacher in Malang, East Java, Indonesia. The data were collected through the teacher’s reflective journals which documented his daily experiences and observations related to using Baamboozle, and a semi structured interview designed to explore the teacher’s perspectives on its benefits, challenges, and future implementation. The findings show that Baamboozle boosted students’ engagement and motivation as the students became more active during the four lessons. However, challenges in relation to preparation time, giving instruction, managing effective grouping, ensuring students’ equal participation, and helping students regulate their emotions were encountered. Despite the challenges, Baamboozle was preferred to be used in the future as an engaging platform that can avoid students’ boredom.